Obtenção da liga quasicristalina Al-Cu-Fe a partir dos elementos reciclados - Fonsêca Júnior, Franklin Lacerda de Araújo (2019)
With the technological advancement of the last decades and the growing research of new materials and processes, the science of materials has assumed an important role in technological innovation worldwide. The diversity of materials currently available for use in engineering is unusually large, with increasingly specialized materials for specific applications. Among these materials, quasicrystalline alloys play an important role due to their unique characteristics, which impels studies and researches to evaluate the stability of this material under severe conditions, development of new alloys, new processing techniques, use of new precursor materials, among others. others. Nowadays, there is an intense need to reduce impacts to the environment and society, given the growing interest in reducing such environmental impacts associated with the technology sector. Based on this premise, a quasicrystalline Al-Cu-Fe alloy was developed, and recycled aluminum was used as the raw material for Al(Rec.)CuFe alloy production; and recycled aluminum, copper and iron for production of the AlCuFe(Rec.) alloy. In this context, aluminum will be obtained through the recycling of coolant / beer cans, copper piping from air conditioning heat exchangers and steel scrap iron from UFPB. The results of X-ray diffraction show that the quasicrystalline phase was still in the crude state, and this phase was even more pronounced as the heat treatments were performed at 750 ºC (1 hour) and 750 ºC (8 hours), the influence of the heat treatment time on the formation of the quasicrystalline phase being evident. The results also showed a small remnant of crystalline phases in the sample with raw material all recycled, due to some contaminant coming from steel of low carbon. SEM images showed the presence of “cauliflower” characteristic of quasicrystalline materials for both alloys. In respect to the hardness, a hardness of 694 HV was obtained for a force of 100 mN for the sample of AlCuFe(Rec.), Treated for 8 h. The sample of Al(Rec.)CuFe for the same force obtained a hardness of 668 HV. The potentiodynamic polarization analyzes for PH = 7 showed a tendency of passivation of both alloys; The methodology was efficient for the production of high purity quasicrystalline alloys, both in the samples with recycled aluminum only and in the samples containing recycled AlCuFe.